2020
DOI: 10.1080/10428194.2020.1786561
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, clinical presentation, and outcomes of Pneumocystis pneumonia when utilizing Polymerase Chain Reaction-based diagnosis in patients with Hodgkin lymphoma

Abstract: A Polymerase Chain Reaction-based diagnosis of Pneumocystis Pneumonia (PCP) and the need for anti-Pneumocystis prophylaxis in Hodgkin Lymphoma patients receiving chemotherapy requires further investigation. This retrospective, single-center, study evaluated 506 consecutive adult patients diagnosed with Hodgkin lymphoma receiving chemotherapy between January 2006 and August 2018. The cumulative incidence of PCP 1 year after start of chemotherapy was 6.2%

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…In addition to the damage to the respiratory system of children, severe pneumonia also causes neurological, digestive, circulatory, and other dysfunctions, as well as cerebral edema, mental confusion, irregular respiratory rhythm, and even respiratory arrest (18)(19)(20). Pneumonia is type of pulmonary edema, with congestion caused by a variety of pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the damage to the respiratory system of children, severe pneumonia also causes neurological, digestive, circulatory, and other dysfunctions, as well as cerebral edema, mental confusion, irregular respiratory rhythm, and even respiratory arrest (18)(19)(20). Pneumonia is type of pulmonary edema, with congestion caused by a variety of pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…This is reiterated by studies that showed prophylaxis did not significantly decrease the incidence of PJP in this patient population [42]. While this is the current recommendation, the overall incidence and mortality associated with PJP in patients treated with ABVD is increased and thus, further research is necessary to clarify the optimal recommendations [41,42]. With regards to patients treated with BV + AVD, rates of PJP have been shown to be low (0.1-1.0%) and PJP prophylaxis is not recommended [39].…”
Section: Pjpmentioning
confidence: 74%
“…At this time, the general recommendation is that PJP prophylaxis is typically not necessary in patients with Hodgkin's lymphoma treated with ABVD [41]. This is reiterated by studies that showed prophylaxis did not significantly decrease the incidence of PJP in this patient population [42]. While this is the current recommendation, the overall incidence and mortality associated with PJP in patients treated with ABVD is increased and thus, further research is necessary to clarify the optimal recommendations [41,42].…”
Section: Pjpmentioning
confidence: 99%